The ankle and an asian pull - Charniga, A. (EWF Scientific Magazine, 2017)
The main distinctions between a Russian pull technique and an Asian pull are the premature heel raise with knees bending and significant deviation of the trunk away from the vertical in the explosion phase of lifting. What would be generally considered a pre - mature raising of the heels in the pull phases of the snatch and the clean on closer examination activate a complex interaction of the body's reactive mechanisms. Concepts such as inertia coupling, transport of power through biarticular muscles and the activation of the windlass mechanism of the foot challenge long accepted ideas of the relative importance of the various muscles and levers to modern weightlifting technique. "We measure the strength of the weightlifter's muscle in poses the lifter assumes during the lifting of the barbell. For instance, sportsmen can generate a force of 300 kg and more in the starting position (A.N. Vorbeyev's data). Weightlifters can generate the largest force in the explosion phase when the knee angles are 130 - 140° and the hip angles are about 60 - 70°, with the barbell at mid - thigh level. Sportsmen can develop a force of 500 kg and more in this position. When the barbell is raised to pelvis level and the elbow angles become 160° the force developed is sharply reduced (200 kg and less). Note: This is an isometric pull flat footed and combined effort of thigh and trunk extensors. Measurements on a force platform have shown that the force developed by qualified weightlifter of the 1st heavyweight class during extension of the legs is 265 - 300 kg (knee angles 135°)." Why shift trunk back behind the vertical line of the bar; raising heels to perform the explosion phase of the pull, instead of employing the Russian protocol, i.e., have the strongest muscles act in concert to raise barbell by straightening legs and trunk with shoulders in front of the barbell. Because the back is weak? Consequently, the Asian pull is poor technique; a manifestation of trunk weakness. Or, on the other hand, the body of the Asian pull devotee, especially the female organism, senses the heel rise and dramatic shifting of the trunk backward is the path of least resistance - overcoming gravity by circumventing a vertical effort.